Private vs. Public Technological Incubator Program - The lesson from Israel - Amnon Frenkel; Dani Shefer; Michal Miller (European Regional Science Association (ERSA), 2005)
The Public Technological Incubator Program (PTIP) was initiated by the Office of the Chief Scientist (OCS) in the Ministry of Industry and Trade in Israel in the wake of a large influx of immigrants from the former USSR, many of whom were scientists and engineers. This massive immigration of highly skilled labor bolstered the Israeli high-tech industry which in the early 1990's blossomed in an unprecedented manner. Between 1990 and 1993, 28 incubators were established. Today there are 24 incubators that are still in operation and they can be found near metropolitan areas and in peripheral areas, as well. Since the year 2000, private technological incubators began operating in Israel. This development owes its activity to the rapidly growing private (venture) capital (VC) that traditionally did not funded such projects. This study examines the differences and similarities between these two types of technological incubators – public vs. private. It addresses the question weather there is still a need for PTIP. The study points to the unique role played by VC funds and private investment companies in sponsoring projects in the private and the public technological incubators. VC funds tend to invest more in projects within private incubators than in projects in public incubators. However, they are only of secondary in importance compare to the financial support rendered by the (CSO) to public incubators and to the owner/sponsor in the private incubators. Thus, these sources of funds serve as complementary rather than as a substitute of funding for projects. Based on our empirical analysis and our findings, the main conclusion is that private incubators cannot substitute public incubators program; even after the entrance of the private sector into the area of technological incubator activity, there is still justification for the continuation of the TPIP. Private incubators tend to concentrate in selected fields while public incubators sponsor a large variety of fields. The PTIP is found to be the only answer to advance national objectives such as the geographical distribution of economic activities and providing special incentives to some selected population groups (such as new immigrants) for whom such activities would otherwise be out of reach.
Keywords: 330